PENGARUH JUMLAH PERCEPATAN RESTITUSI PAJAK PERTAMBAHAN NILAI TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI (Studi pada Kantor Pelayanan Pajak Pratama Malang Utara) - Anjarwi, Astri Warih; Kharisma, Linda (Profit: Jurnal Adminsitrasi Bisnis, 2021)
The Accelerated of Value Added Tax Restitution is Indonesian government’s policy to a preliminary refund of value added tax overpayment. The simplification or the acceleration of the provision of restitution is done without strict examination and long process, but by simple research. Accelerated restitution policy is given to the Taxpayer who fulfills certain requirements (certain amount of restitution as mentioned above), certain criteria (Taxpayers who comply) and they are low risk Taxable Entrepreneurs that determined by the Minister of Finance. The Acceleration of Value Added Tax restitution is expected to reduce the cost compliance because the provision of restitution is done without examination and it is hoped that this policy could increase cash flow and liquidity of the economy. The research’s purpose is determine to impact the number of acceleration of value added tax restitution to the acceptance of value added tax. The type of research is explanatory research with a quantitative approach. The research’s data is secondary data that obtaine from the Pratama Tax Office Malang Utara. The research’s  data is time series data during the periode of April 2018 – November 2019. The data analysis technique on the research is a simple regresi linier analysis. The results of this research is variable number of acceleration restitution on value added tax impact and significant for the revenue value added tax in the Pratama Tax Office Malang Utara. The value of R Square earned is 0.374 which means that the number of accelerated restitution of value added tax has an impact on the variable revenue of value added tax is 37.4%.